From cup to dish: how to make and use endometrial organoid and stromal cultures derived from menstrual fluid - Hewitt, Sylvia C.; Dickson, Mackenzie J.; Edwards, Nicole; Hampton, Kathleen; Garantziotis, Stavros; DeMayo, Francesco J. (Frontiers in Endocrinology, 2023)
Diseases impacting the female reproductive tract pose a critical health concern. The establishment of in vitro models to study primary endometrial cells is crucial to understanding the mechanisms that contribute to normal endometrial function and origins of disease. Established protocols for endometrial stromal cell culture have been in use for decades but recent advances in endometrial organoid culture have paved the way to allowing study of the roles of both epithelial and stromal endometrial cells in vitro. Due to inter-individual variability, primary cell cultures must be established from numerous persons. Generally, endometrial epithelial and stromal cells can be isolated from an endometrial biopsy, however this is collected in a clinical setting by an invasive transcervical procedure. Our goal was to develop a non-invasive method for isolation of paired endometrial epithelial organoids and stromal cells from menstrual fluid collected from individual women, based on recent reports describing isolation of endometrial epithelial organoids or endometrial stromal cells from menstrual fluid. Participants recruited by the NIEHS Clinical Research Unit were provided with a menstrual cup and instructed to collect on the heaviest day of their menstrual period. Endometrial tissue fragments in the menstrual fluid samples were washed to remove blood, minced and digested with proteinases. Following digestion, the solution was strained to separate epithelial fragments from stromal cells. Epithelial fragments were washed, resuspended in Matrigel, and plated for organoid formation. Stromal cells were separated from residual red blood cells using a Ficoll gradient, then plated in a flask. Once established, estrogen responsiveness of endometrial epithelial organoids was assessed and decidual response of stromal cells was evaluated. Following treatments, qPCR was performed on organoids for genes induced by estradiol and on stromal cells for genes induced by decidualization. In this manner, relative responsiveness of paired organoid and stroma cell cultures isolated from each woman can be assessed. In conclusion, we can isolate both epithelial and stromal cells from a single menstrual fluid sample, allowing us to establish organoids and cells in a paired manner. This protocol can greatly enhance our knowledge of the role of epithelial and stromal cells alone and in coordination.